ELT Undergraduate Program Alumnus’ Perception towards Project-Based Learning Experience - Larasati, Annisa; Harianti, Lisa Ramadhani (Universitas Negeri Malang, 2023)
Project-based learning as one of the recent innovations in teaching and learning methodology has been introduced rapidly in many higher institutions in Indonesia. In general, project-based learning consists of several steps: (1) driving questions, (2) situated inquiry, (3) collaboration, (4) integration of technology, (5) creating learning product. This methodology is a part of contextual teaching and learning, a learning approach that emphasizes the students’ interest and experiences and provides the means for reaching learning goals that requires higher order thinking skills. One example of the implementation of project-based learning happens in English Language Teaching study program in Department of English, Universitas Negeri Malang. This study program has equipped its students to experience this methodology in various courses both skill courses and content courses. Employing descriptive qualitative research method, this study investigated the perception of ELT UM alumnus about their experiences in their undergraduate degree program using project-based learning. This study involved 30 participants whom are the undergraduate alumni from ELT study program from year 2015-2019. The instrument used in this study were questionnaire for all participants and in-depth interview on some of the participants. The result and discussion section are classified into six sub-topics: strategies employed in teaching and learning process, critical thinking in PBL, collaboration in PBL, supporting tools in PBL, final product in PBL, and affective impact of PBL. It is expected that from this study, other researchers may get some insights to develop more understanding on project-based learning, while for teachers as facilitators may get some practical idea to implement this methodology in their teaching and learning process.